Feasibility of using the Multinational Association of Supportive Care in Cancer antiemesis tool for assessment of chemotherapy-induced nausea and vomiting at Institute for Oncology and Radiology of Serbia and palliative care team - Bakić N.; Dimitrijević J.; Bošnjak S. (Association of Nurses Technicians and Midwives, 2015)
Introduction: Chemotherapy-induced nausea and vomiting (CINV) has been shown to adversely impact patient anxiety, quality of life, treatment adherence, and use of health care resources. The Multinational Association of Supportive Care in Cancer (MASCC) has developed a tool (MASCC Antiemesis Tool (MAT)) to improve assessment and subsequent management of CINV by enhancing communication between patients and their clinicians. This study assessed the feasibility of using the MAT in patients at the Institute for Oncology and Radiology of Serbia. The secondary objective was to describe the incidence of CINV as identified by the tool. Methods and materials: This study involved a prospective survey using the MAT in patients receiving intravenous chemotherapy. Subjects completed the MAT twice post-chemotherapy regarding CINV symptoms and returned it at their next clinic appointment. Participants were also surveyed to evaluate feasibility with regard to using the MAT. Results: Of the 35 patients recruited, 57% returned surveys. The majority of patients reported that the MAT facilitated communication with their clinician, particularly those who had experienced CINV 70% of patients who returned the MAT reported CINV; however, less than half of them had received antiemetic drugs according to the recommendations contained in international guidelines. Only four patients with CINV had antiemetic changes made for subsequent cycles. Conclusion: The MAT is a feasible tool which can improve communication of CINV symptoms between patients and clinicians, a foundational step toward improving CINV management.